PENGGUNAAN APLIKASI DALAM MEMONITOR DAN MENCEGAH STUNTING - Manginar Sidabutar; Friska D. Simamora; Fitri A.Ramli (Bajang Institute, 2025)
Stunting is a fairly serious public health problem,especially developing countries including Indonesia.Data from Indonesian Ministry of Health (2018) shows the prevalence stunting in Indonesia is 30.8%.Stunting is a condition when a child has height shorter than average height of children the same age. Stunting usually occurs in children who do not get enough nutrition during the first thousand days of their lives,namely from pregnancy to the age of 2 years.As many as 23% of babies are born with stunting conditions in NTT and the remaining 77% become stunted after birth or postnatal.In efforts to prevent stunting in infants,the role information technology can utilized to conduct surveillance and monitoring of infants' diet and health conditions such as morbidity,vitamin A consumption,additional food,immunization and neonatal visits can be obtained in real time.Objectives Reducing stunting rates in West Kupang District NTT.This activity expected to beneficial mothers who have babies less than 1 year old,in helping to prevent stunting their babies.This research also useful for health workers obtaining data on the practice Viding 1 year old babies,infections experienced by babies and the health facilities.The results of the data obtained there were 7 pregnant women with 3 of them included in the KEK category with an average of pregnant women weighing less than 50 kg,the irregular eating patterns of pregnant women,and also unhealthy lifestyle that always ignores eating on time during pregnancy.For dental health, pregnant women are categorized as quite good because their OHIS still relatively good.Conclusion The occurrence of LBW or stunting in West Kupang District is not due to lack of sufficient food supplies but is due to the lifestyle pregnant women who are lazy to eat because they are always disturbed by nausea and vomiting every day so that they decide not to eat,or eat only once a day